Quantum Mechanics, Time, and Theology: Indefinite Causal Order and a New Approach to Salvation - Qureshi-Hurst, Emily ca. 20./21. Jh. (Zygon, 2020)
Quantum mechanics has recently indicated that, at the fundamental level, temporal order is not fixed. This phenomenon, termed Indefinite Causal Order, is yet to receive metaphysical or theological engagement. We examine Indefinite Causal Order, particularly as it emerges in a 2018 photonic experiment. In this experiment, two operations A and B were shown to be in a superposition with regard to their causal order. Essentially, time, intuitively understood as fixed, flowing, and fundamental, becomes fuzzy. We argue that if Indefinite Causal Order is true, this is good evidence in favor of a B-theory of time, though such a B-theory requires modification. We then turn to theology, suggesting that a B-theoretic temporal ontology invites serious reconsideration of the doctrine of salvation. This paper concludes that the best explanation for salvation given a B-theory is mind-dependent salvific becoming, a type of psychological soteriological change that occurs through downward causation.